Formation of novel polycyclic P-S-P linked complex through an unexpected stepwise [4+4] cycloaddition. - Lin, Yu Han. (2010)
In this project we wish to report our findings on the synthesis of a P-S-P linked bidentate ligand, compound 1 from the precursor, bis[(3,4-dimethylphosphole) pentacarbonyltungsten]sulfide, 2. While in the preparation of compound 2, it was discovered that undergoes a [2+2] cycloaddition to form 3, followed by a rearrangement to form compound 4. Overall, compound 2 undergoes a stepwise [4+4] cycloaddition to form compound 4. Synthesis of compound 4 was found to work best with visible light irradiation using dichloromethane as the solvent. Converting compound 2 to 1 by reaction with DMAD to form the bis-7-phosphanobornadiene complex was unsuccessful. Creating asymmetrical P-S-P linked phosphinidene sources was attempted by making use of previous discovery that [1-chlorophosphirane] pentacarbonyltungsten generates the terminal phosphinidene upon heating. Compound 5 was synthesized in the process which dimerized to compound 2. The last of the attempts failed as the protected thiophosphole (compound 6) did not form the 7-phosphanobornadiene due to steric bulk, preventing the Diels-Alder Cycloaddition. Finally, attempts were made to desulfurize or decomplex compound 4 in hope of formation of a new polycyclic bidentate ligand in use for catalysis.